Hydrogen Peroxide‐Induced Oxidative Dimerization of Wittig Reagents: Improving the Selectivity, Yield and Expanding to the Aryl System. Issue 24 (28th August 2017) - He, Wei; Lv, Yue‐Guang; Hong, Tian‐Yu; Tong, Yuan‐Bo; Zhu, Zhong‐Peng; Wei, Qian; Guo, Cun‐Yue; Yu, Gui; Yang, Jing‐Kui
Abstract: Under the protection of nitrogen, the use of THF as best solvent can increase the yield or stereoselectivity of the H2 O2 induced oxidation of Wittig reagents to give the corresponding dimerization products ( trans ‐alkenes) as the major or only product in better to good yields up to 98 %. This reaction can be expanded to the aryl system in the yield up to 94 % for homo‐coupled dimers or 58 % for cross coupled dimers. This result will expand the synthetic application scope of Wittig reagents and H2 O2 . Abstract : THF as solvent combined with the N2 protection can improve the H2 O2 induced oxidative dimerization of Wittig reagents, the yields (up to ∼98 %) and stereoselectivity ( trans as major one) of the products were better than the literature, and also the scope of this reaction can be expanded to more aryl keto derivatives. (yields: 26∼94 %).